2020
DOI: 10.32620/aktt.2020.6.01
|View full text |Cite
|
Sign up to set email alerts
|

Topological Designing and Analysis of the Composite Wing Rib

Abstract: The composite structures in the aerospace industry for in recent decades are widely applied however, at the beginning of the 21st century composites are growing rapidly. The largest companies in the aerospace industry are increasing the volume of composites application of in the structures, and nowadays the volume of composites reaches 50%. The different elements of aircraft and even highly loaded structures such as spars, ribs, skin, etc., are currently made from composites. First of all, this is due to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…A method was proposed to effectively reduce the bending deformation of airfoils at a high aspect ratio. Hu and Vambol [22] optimized the rib of a symmetric laminate using a topology model. The deformation of the material was successfully reduced by 20% through the optimization of different fiber orientations.…”
Section: Introductionmentioning
confidence: 99%
“…A method was proposed to effectively reduce the bending deformation of airfoils at a high aspect ratio. Hu and Vambol [22] optimized the rib of a symmetric laminate using a topology model. The deformation of the material was successfully reduced by 20% through the optimization of different fiber orientations.…”
Section: Introductionmentioning
confidence: 99%
“…-topological optimization of geometry and structure [4,5]; -a quick transition from a model to its implementation. The issue related to fabricating a structure that should comply with certain requirements by 3D printing is similar in many aspects to the problems related to manufacturing structures from composite materials [6]:…”
Section: Introductionmentioning
confidence: 99%
“…Hu and Vambol [11] designed the composite wing rib based on the topology optimization method, and the results show that the deformation of the optimized structure can be decreased by more than 20% compared with that of the non-optimized structure under the same material removal rate. The above results showed that the fiber orientation greatly affects the structural performances and topological shape.…”
Section: Introductionmentioning
confidence: 99%